Green chemistry handbook - Doyle, Simon (New York, NY, USA NY Research Press, 2015)
Green and sustainable chemistry is the need of the hour. The degradation of the environment by any means, needs to be stopped. This book covers in detail some innovative concepts and case studies which have been developed in the field of green and sustainable chemistry. This book is a vital tool for all researching or studying this area as it includes research works on contemporary theories in this field.
Includes bibliographical references.
Keywords: Environmental chemistry -- Industrial applications -- Research; Green chemistry -- Research; Sustainable engineering -- Research